SOSIALISASI SISTEM TIGA STRATA (STS) UNTUK MENGATASI MASALAH HIJAUAN MAKANAN TERNAK PADA PETANI TERNAK SAPI PERBIBITAN DI DESA SAKTI, NUSA PENIDA - Wirawan, I.W.; Utam, I.A.P.; Susila, T.G.O.; Kayana, I G. N. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi)
Socialisation Three Strata System (STS) forages purpose is to overcome the problem of forage fodder in cattle breeding farmers in the Village of Sakti, District Nusa Penida, through the introduction of the system of three strata, so the availability of forage cattle food available throughout the year. Through this service, the expected cattle breeding group members have the knowledge and skills of the system of three strata (STS) forages and rice straw fermentation technology to improve the nutritional value of rice straw as cattle feed, especially in dry season. Activity results showed that participants' knowledge about Three Strata Systems (STS) forages and skills about biofermentation techniques to improve the nutritional content of rice straw as an alternative cattle feed were increased by 20,35%. It can be concluded that the knowledge and skills of cattle breeding farmers were increased after being given the training the introduction of the system of three strata for availabiliting of forages cattle food available throughout the year and to use the fermentation technique.
Keywords: three strata system (STS) forages, rice straw, fermentation, cattle, and feed